Influence of electron irradiation on spectra of light electroreflection from the surface of Ge/Ge₁₋xSix heterostructure - Abbasov, Sh.M.; Aghaverdiyeva, G.T.; Ibrahimov, Z.A.; Farajova, U.F.; Ibrahimova, R.A.; Mehdevi, Heyder (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
In this work, the growth properties of Ge₁₋xSix epitaxial films grown on Ge substrates were investigated. The structural perfection of the films was controlled by electron diffraction, electron microscopic and X-ray diffraction methods. It has been established that the surface structure of the sample Ge/Ge₁₋xSix changes after irradiation by accelerated electrons Ф = 5×1016 cm⁻², and generated are surface defects which play the role of traps for change carriers.